2000
DOI: 10.1152/ajprenal.2000.279.5.f919
|View full text |Cite
|
Sign up to set email alerts
|

PKA site mutations of ROMK2 channels shift the pH dependence to more alkaline values

Abstract: Close similarity between the rat native low-conductance K(+) channel in the apical membrane of renal cortical collecting duct principal cells and the cloned rat ROMK channel strongly suggest that the two are identical. Prominent features of ROMK regulation are a steep pH dependence and activation by protein kinase A (PKA)-dependent phosphorylation. In this study, we investigated the pH dependence of cloned renal K(+) channel (ROMK2), wild-type (R2-WT), and PKA site mutant channels (R2-S25A, R2-S200A, and R2-S2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
2
46
0
Order By: Relevance
“…balance (13), a correlation attributed to the exquisite sensitivity of ROMK1 to cytosolic pH (37)(38)(39)(40). In face of the present observations, it is appealing to speculate that NHERF2 participates in the regulation of K ϩ excretion by acid base balance.…”
Section: Discussionmentioning
confidence: 59%
“…balance (13), a correlation attributed to the exquisite sensitivity of ROMK1 to cytosolic pH (37)(38)(39)(40). In face of the present observations, it is appealing to speculate that NHERF2 participates in the regulation of K ϩ excretion by acid base balance.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, single channel experiments revealed that the different PKA phospho-acceptors regulate the channel through different mechanisms (15). Phosphorylation of the two COOHterminal sites are required to maintain the channel in a high open probability state (15), controlling both pH-dependent gating (16) and phosphatidylinositol 4,5-biphosphate-dependent activation of the channel (17). Phosphorylation of the NH 2 -terminal site, on the other hand, has no effect on channel open probability.…”
Section: From the Department Of Physiology University Of Maryland Scmentioning
confidence: 99%
“…Activity of the Kir1.1 channel is directly regulated by intracellular pH, protein kinase A, protein kinase C, phosphatidylinositol-4,5-biphosphate, and WNK4 (serine-threonine kinase 4 with no lysine) (8 -11). Inhibition of protein kinase A activity or phosphatidylinositol-4,5-biphosphate production shifts the channel sensitivity toward more alkaline pH levels (12,13).…”
Section: Kir11 (Romk1) Is a Member Of The Inward Rectifier Kmentioning
confidence: 99%